Study Communicate of Information technology in The Export of Agricultural Products of Karbala Province - Havall Muhssin Mohammad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
One of the most important consequences of globalization is increased competition at the international level of economics. Because in these circumstances, we will always face reduced transportation costs, the astonishing growth of information technology and increasing expansion of e-commerce and minimization of geographical constraints and growth of competition, which will increase the efficiency of the international economy. Among these, it can be said that the most important consequence of globalization on the economies of countries is the growth of e-commerce. The agricultural sector in most developing countries, including Iran, plays an important role in the trading system, GDP and job creation. The use of e-commerce in this major part of the national economy will bring great benefits, so to use this new technology, it is necessary to provide a feasibility study for the development of e-commerce in the export of agricultural products in this study. The present research method is descriptive-survey and is also applied in terms of the type of research because its results can be useful for the development of e-commerce in the export of agricultural products in the cities of Karbala province. In this study, employees and export specialists of the Commercial Organization, Agricultural Jihad, Chamber of Commerce and Industries and Deputy, brokers and natural and legal persons are engaged in agricultural exports and farmers of Karbala province as a statistical community. The method of random sampling was simple that after determining the sample size, the samples were randomly selected from the study population and finally 170 questionnaires were distributed among the statistical population. Both descriptive and inferential statistical methods were used to test and analyze the processed information and were based on the SPSS software package. The results showed that technically, economically, legally, operationally and temporally, the possibility of developing e-commerce in the export of agricultural products There is Karbala province and the importance and role of these factors in the development of e-commerce in the export of agricultural products in the cities of Karbala province is not the same. This means that the technical factor in the development of e-commerce is most important in the export of agricultural products in the cities of Karbala province, then the economic factor, then the time factor, then the operational factor and finally the legal factor